'We Have Equal Opportunities – in Theory': Lay Perceptions of Privilege, Meritocracy and Inequality in Denmark. (December 2021) - Andersen, Ditte; Lue Kessing, Malene; Østergaard, Jeanette
This article reports on the findings from a qualitative, longitudinal study on lay perceptions of opportunity structures among young adults in Denmark. Previous research suggests that people often underestimate the extent of inequality and that rising inequality aggravates misperceptions. Our study deepens the understanding of the multi-layered processes that form meritocratic beliefs, and it identifies key factors at the macro-, meso- and micro-level. A macro-level factor that proved influential was a cultural script revolving around the Danish lay concept, social arv [social inheritance]. At the meso level, the factor of reference groups in socio-economic heterogeneous schools was instrumental for formations of inequality perceptions, but in dissimilar ways depending on micro-level subjective factors. Overall, the participants viewed the free educational system in Denmark as part of a welfare system that equalises opportunity structures in principle, while the majority simultaneously exhibited a nuanced awareness of social forces negating meritocracy in practice .